Uncertain Geography of the Local News and Civic Participation in New Media Era - Steblyna, Nataliia (Communication Today, 2018)
New technologies give local journalists the opportunity to extend their agenda, adding the international context; however, for community participation it is crucial to be informed about the closest environment. Several Ukrainian local news sites in the situation of political instability and military conflict increase the number of news items about international/national issues, whereas a majority of others covers predominantly city/ regional events. On the basis of content analysis, news geography of two leading news sites of two Ukrainian cities Lviv and Odesa are studied and two types of local sites are discovered: local (with a high priority given to the local news) and non-local (with a priority placed on the international and national news). A clear correlation between the number of texts and exclusivity of news sources can be seen. Exclusivity is higher on the sites which see the local news items as their priority; however, quality of news remains problematic for both types. Readers are provided with a lot of unchecked and unbalanced content. As a result, functions of community integration